Bioabsorbable radiopaque water responsive shape memory polymer-hydrogel composite device for temporary vascular occlusion in liver cancer treatment - Salvekar, Abhijit Vijay (2018)
Hepatocellular carcinoma (HCC) is the second most reason of cancer related death worldwide (approximately 800,000 deaths globally per annum). Whilst the surgery is the only curative way, only 10% of primary and metastatic liver cancer patients are eligible for resection while the remaining patients can only opt for palliative treatments such as transarterial chemo embolization (TACE). TACE treatment requires temporary embolization/blocking of hepatic artery, which accounts for 90% blood supply of tumor. Repeat sessions at six- to twelve-weeks intervals of the treatment are recommended, so patency of the hepatic artery needs to be restored before next treatment. Use of biodegradable embolic agent holds great promise for this application. Most of the embolic device available in the market are metallic. In this regard, Gelfoam is the most widely used biodegradable embolic agent for intravascular embolization, but their use is associated with some problems such as unpredictable occlusion level, non-target embolization and inaccurate placement, uncontrolled degradation, permanent occlusion (at times) etc. We have proposed biodegradable shape memory polymer-hydrogel composite as an embolic agent which will prevail over above-mentioned limitations of Gelfoam. The proposed embolic device consists of biodegradable Poly(DL-Lactide-co-Glcolide) (PLGA) filament coated with Polyethylene Glycol (PEG) hydrogel. The main objective of this research work is to understand the water induced buckling mechanism of the PEG hydrogel and to use it for making a shape memory embolic device which can be activated on contact with body fluid at body temperature to facilitate occlusion of a blood vessel. To do so, in this work shape memory characteristics of individual components poly(dl-lactide-co-glcolide) and polyethylene glycol hydrogel were investigated. PLGA evinces thermo responsive shape memory around body temperature. Different PLGA compositions with the varying amount of plasticizer and radiopaque fillers were extruded in filament form with the objective of having a filament with shape memory effect and radiopacity at body temperature. These compositions were characterized for thermal, mechanical, shape memory, and radiopacity in order to find the optimized composition. From the studies, it was found that the PLGA formulation with 2% plasticizer and 50% bismuth oxychloride exhibited the optimal properties. Mechanical and swelling characteristics of different hydrogel formulations were studied to investigate the effect of different parameters such as PEG concentration, initiator concentration, and crosslinking time. Shape memory effect and shape change effect in dry PEG hydrogel were studied individually. Buckling mechanism of the PEG hydrogel filament, synthesized using photo-crosslinking method was explored and correlated to several factors, including the extent of strain, deformation temperature, and diameter of the sample. Parameters to control buckling of the PEG hydrogel were identified and validated using theoretical modeling and experimental results. It was found that the original diameter and amount of pre-stretching are identified as two influential parameters to tailor the buckling time as confirmed by both experiments and simulation. The polymer-hydrogel composite was then fabricated using optimized formulation and conditions derived from the individual characterization results of the PLGA and PEG hydrogel. Fabricated device samples programmed for water induced shape memory using melting transition temperature of the PEG. In-vitro performance of the device was investigated using simulated flow model, with 100% occlusion being achieved within 2-3 minutes of deployment. Performance characteristics of the device such as stability in flow, degradation, cytotoxicity, hemocompatibility and shelf life were investigated. The cytotoxicity and hemocompatibility studies indicated good biocompatibility and non-hemolytic properties of the embolic plug. The shelf life studies confirmed the mechanical integrity of the device as well as no loss of shape memory properties over a period of six months. Finally, a feasibility study was conducted in- vivo in a rabbit model to investigate the ease of device deployment, device migration and extent of vessel occlusion. In-vivo studies in rabbit model evinced successful deployment of the new embolic plug using the existing method and complete occlusion at a targeted location of the vessel was achieved in less than two minutes.